BRAND SIWTCHING INTENTION AMONG MALAYSIAN SMARTPHONE USERS: A PUSH-PULL-MOORING PERSPECTIVE - Xi-Min Koo; Ahmad Zainal Abidin Abd Razak, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2023)
This study aims to investigate factors that lead to brand switching intention among Malaysian smartphone users, specifically using the Push-Pull-Mooring model. Push factors are understood as the negative factors that push people away from the original provider while pull factors are the positive factor that attract people towards a new provider. As for mooring factor, it includes the lifestyle, cultural and personal factors that affect the switching intention. The push factors included in the study are price and dissatisfaction. Meanwhile, mooring factors include variety seeking and social influence. On the other hand, attractiveness of alternative is considered as the pull factor for this study purpose. Quantitative approach through self-administered questionnaire is employed in this study. The targeted respondents are Generation Y smartphone users, and the survey was carried out in Kuala Lumpur. Data Analysis was done using IBM SPSS Statistic 24 and AMOS 22. The findings revealed that social influence and attractiveness of alternatives were the factors that highly affect the brand switching intention. Other factors which include price, dissatisfaction, and variety seeking were also found to be factors leading to the switching intention although their results are not as significant as compared to the other two. This study offers valuable insights to smartphone companies to better understand the factors that contribute to brand switching. It allows empowerment of the companies to further improve on various aspects and ultimately foster brand loyalty, which is vital for long-term success in the smartphone industry